Replacing alfalfa hay with industrial hemp ethanol extraction byproduct and Chinese wildrye hay: Effects on lactation performance, plasma metabolites, and bacterial communities in Holstein cows - Wang, Yiqiang; Yu, Qingyuan; Wang, Xiaolin; Song, Jiamei; Lambo, Modinat Tolani; Huang, Jianguo; He, Ping; Li, Yang; Zhang, Yonggen (Frontiers in Veterinary Science, 2023)
This trial was designed to investigate the effects of industrial hemp ethanol extraction byproduct (IHEEB) and Chinese wildrye hay (CWH) replacement of alfalfa hay (AH) on digestibility, and lactation performance, plasma metabolites, ruminal fermentation, and bacterial communities in Holstein dairy cows. Nine healthy multiparous Holstein cows (parity = 3) with similar body weights (584 ± 12.3 kg), days in milk (108 ± 11.4), and milk yields (30 ± 1.93 kg; all mean ± standard deviation) were used in a replicated 3 × 3 Latin square design with 3 periods of 21 d. During each period, each group consumed 1 of 3 diets: (1) 0% IHEEB (0IHEEB); (2) 6.0% IHEEB and 1.7% Chinese wildrye hay (6IHEEB); (3) 10.8% IHEEB and 4.3% Chinese wildrye hay (11IHEEB). The diets in each group were isocaloric and isonitrogenous, with similar contents of concentrate and silage but different ratios of IHEEB and CWH to replace AH. The results showed that increasing the substitute did not affect the total-tract apparent nutrient digestibility. There was no difference in lactation performance of dairy cows fed the three diets, except for the cows' somatic cell count (SCC), which decreased with the increase in the amount of the substitute. Cannabidiol and tetrahydrocannabinol were not detected in milk samples of dairy cows in the different treatment groups. 6IHEEB and 11IHEEB-fed cows showed a linear decrease in total volatile fatty acids (VFA) and butyrate compared to the 0IHEEB cows. Plasma IL-1β content quadratically decreased with feeding IHEEB and CWH, and other blood parameters were unaffected. The rumen fluid's relative abundances of Bacteroidota, Fibrobacterota, and Prevotellaceae quadratically increased, while Firmicutes tended to decrease quadratically as the substitution increased. Feeding IHEEB and CWH linearly increased the relative abundances of Firmicutes, Lachnospiraceae, Monoglobaceae, and Butyricicoccaceae in the feces. As the substitution increased, the cost of dairy farming was reduced. In summary, substituting AH with IHEEB and CWH in diets did not affect the total-tract apparent nutrient digestibility, improved milk composition, and plasma immune indices. It changed the bacterial composition in rumen fluid and feces and improved dairy farming benefits.